Blastic Plasmacytoid Dendritic Cell Neoplasm: A Rare Case Report with Literature Review - Oza, Nikita; Rathnam, Krishnakumar; Sumeet, Gujral; Honey, Susan R.; Saju, S. V.; Shubhada, Kane (Indian Journal of Medical and Paediatric Oncology, 2021)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematopoietic neoplasm for which there are no effective therapies. We present a 70-year-old male patient with multiple reddish painless, nonpruritic, and nonpedunculated nodules over the trunk, forearm, and thighs for a duration of 3 months. The nodules measured 0.5 to 2 cm in diameter. The peripheral smear findings were within normal limits. Excision biopsy was performed. Histomorphology and immunohistochemistry (CD123, CD 56, CD4, HLA-DR, CD43, and CD68) confirmed the diagnosis of BPDCN. Findings of marrow aspiration, biopsy and imaging studies were within normal limits. Patient demonstrated a good response with complete disappearance of all nodules by initial 2 weeks of therapy with a modified Berlin–Frankfurt–Munster (BFM) acute lymphoblastic leukemia (ALL) protocol and has completed 8 doses (LSAP [lincosamides, streptogramins A and pleuromutilins chemotherapy], 5,000 units/m2). The patient tolerated protocol extremely well.
Keywords: blastic plasmacytoid dendritic cell neoplasm; chemotherapy; stem cell therapy; targeted therapy